Electricity markets and renewables : emissions, costs and fuel diversity - O'Mahoney, Amy (Trinity College (Dublin, Ireland). Department of Economics, 2013)
As energy consumption has risen steadily over the past century, so too have emissions, contributing to climate change. Energy consumption is a necessary aspect of economic growth - it is an input into the production of goods and services, the creation of capital stock, and for the development of technological progress. As electricity is a requirement in all households and industries, the price paid for electricity directly affects the monetary and fiscal structure of nations. While climate change; and overconsumption of fossil fuels are not optimal outcomes, the approach governments and policy makers should take to address these issues is not clear cut. The market will not reach sustainable levels of emissions output and fossil fuel consumption without intervention, yet such intervention must be politically and administratively feasible. Thus, any policy alternatives based on reducing emissions output and fossil fuel consumption must be considered within the context of wider policy issues such as competitiveness and consumer welfare. This thesis examines various energy policies under the three objectives of sustainable cost, emissions reduction and security of supply, discussed in the context of the Irish electricity market. In order to examine electricity market costs, this dissertation examines if inappropriate bidding behaviour by generators in the Irish electricity marked is a driver of high Irish electricity prices. The research finds that generators are bidding appropriately, with generators bidding the spot price of their inputs correctly in the regression model, and this behaviour remaining constant over the course of the day and varying levels of demand.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin.